Unusual strategies for using indium gallium nitride grown on silicon (111) for solid-state lighting - Kim, Hoon-sik (National Academy of Sciences, 2011)
Properties that can now be achieved with advanced, blue indium gallium nitride light emitting diodes (LEDs) lead to their potential as replacements for existing infrastructure in general illumination, with important implications for efficient use of energy. Further advances in this technology will benefit from reexamination of the modes for incorporating this materials technology into lighting modules that manage light conversion, extraction, and distribution, in ways that minimize adverse thermal effects associated with operation, with packages that exploit the unique aspects of these light sources. We present here ideas in anisotropic etching, microscale device assembly/integration, and module configuration that address these challenges in unconventional ways. Various device demonstrations provide examples of the capabilities, including thin, flexible lighting “tapes” based on patterned phosphors and large collections of small light emitters on plastic substrates. Quantitative modeling and experimental evaluation of heat flow in such structures illustrates one particular, important aspect of their operation: small, distributed LEDs can be passively cooled simply by direct thermal transport through thin-film metallization used for electrical interconnect, providing an enhanced and scalable means to integrate these devices in modules for white light generation.